KEBIJAKAN PEMERINTAH HINDIA BELANDA TERHADAP PENDIDIKAN KAUM BANGSAWAN DI INDONESIA ( 1900-1920) - Siregar, Erwin (JURNAL EDUCATION AND DEVELOPMENT, 2016)
This research aims to know state of the implementation of the Dutch East Indies government ability in the field of education for the nobility Indonesia in 1900-1920. The method is the historical research methods. The collection data technique used documentation an literation study, while the analysis of the data used is analysis of qualitative data. The results showed that the Dutch East Indies Governmentâs education policy is given to the Indonesian people are preferred for the nobility Bumiputera. Dutch East Indies government policy of education for the nobility in Indonesia is in the form of the estabilishment of school institution. School that established by the Ducth Government for the nobility in Indonesia, among which: ELS.